Phytoremediation technologies and their mechanism for removal of heavy metal from contaminated soil: An approach for a sustainable environment - Sharma, Jitendra Kumar; Kumar, Nitish; Singh, N. P.; Santal, Anita Rani (Frontiers in Plant Science, 2023)
The contamination of soils with heavy metals and its associated hazardous effects are a thrust area of today’s research. Rapid industrialization, emissions from automobiles, agricultural inputs, improper disposal of waste, etc., are the major causes of soil contamination with heavy metals. These contaminants not only contaminate soil but also groundwater, reducing agricultural land and hence food quality. These contaminants enter the food chain and have a severe effect on human health. It is important to remove these contaminants from the soil. Various economic as well as ecological strategies are required to restore the soils contaminated with heavy metals. Phytoremediation is an emerging technology that is non-invasive, cost-effective, and also aesthetically pleasing. Many metal-binding proteins (MBPs) of the plants are significantly involved in the phytoremediation of heavy metals, the MBPs include metallothioneins (MTs), phytochelatins (PCs), metalloenzymes (MEs), metal-activated enzymes, and many metal storage proteins, carrier proteins, and channel proteins. Plants are genetically modified to enhance their phytoremediation capacity. In Arabidopsis, expression of ion binding protein of mercuric (MerP) in Bacillus megaterium improves the metal accumulation capacity. Also, the phytoremediation efficiency of plants is enhanced when assisted with microorganisms, biochar, and/ or chemicals. Removing heavy metals from agricultural land without challenging food security is almost impossible. As a result, crop selections with the ability to sequester heavy metals and provide food security are in high demand. This paper summarizes the role of plant proteins, and plant–microbe interaction in remediating soils contaminated with heavy metals. Biotechnological approaches or genetic engineering can also be used to tackle the problem of heavy metal contamination.